Patient Specific Computer Modelling for Automated Sizing of Fenestrated Stent Grafts. (February 2020) - Derycke, Lucie; Sénémaud, Jean; Perrin, David; Avril, Stephane; Desgranges, Pascal; Albertini, Jean-Noel; Cochennec, Frederic; Haulon, Stephan
Abstract : Objective: The aim was to validate a computational patient specific model of Zenith® fenestrated device deployment in abdominal aortic aneurysms to predict fenestration positions. Methods: This was a retrospective analysis of the accuracy of numerical simulation for fenestrated stent graft sizing. Finite element computational simulation was performed in 51 consecutive patients that underwent successful endovascular repair with Zenith® fenestrated stent grafts in two vascular surgery units with a high volume of aortic procedures. Longitudinal and rotational clock positions of fenestrations were measured on the simulated models. These measurements were compared with those obtained by (i) an independent observer on the post-operative computed tomography (CT) scan and (ii) by the stent graft manufacturer planning team on the pre-operative CT scan. (iii) Pre- and post-operative positions were also compared. Longitudinal distance and clock face discrepancies >3 mm and 15°, respectively, were considered significant. Reproducibility was assessed using Bland–Altman and linear regression analysis. Results: A total of 195 target arteries were analysed. Both Bland–Altman and linear regression showed good reproducibility between the three measurement techniques performed. The median absolute difference between the simulation and post-operative CT scan was 1.0 ± 1.1 mm for longitudinal distance measurements and 6.9 ± 6.1° for clock positions. The median absolute difference between the planning centre and post-operative CT scan was 0.8 ± 0.8 mm for longitudinal distance measurements and 5.1 ± 5.0° for clock positions. Finally, the median absolute difference between the simulation and the planning centre was 0.96 ± 0.97 mm for longitudinal distance measurements and 4.8 ± 3.6° for clock positions. Conclusion: The numerical model of deployed fenestrated stent grafts is accurate for planning position of fenestrations. It has been validated in 51 patients, for whom fenestration locations were similar to the sizing performed by physicians and the planning centre.